Ways of upgrading optical-electronic reconnaissance and aiming weapons and military equipment - Kondrat, V.; Kostenko, O.; Kutsenko, V. (Radiotekhnika, 2018)
A comparative analysis of existing and prospective (modernized) optical-electronic means of night and day vision is carried out. The ways of their modernization are proposed in order to create an integrated automatic decision-making system for the destruction of targets for weapons and military equipment samples of the National Guard of Ukraine.